Error traps in pediatric difficult airway management. Issue 12 (14th September 2021) - Sohn, Lisa; Peyton, James; von Ungern‐Sternberg, Britta S; Jagannathan, Narasimhan
Abstract: Difficult airway management in children is associated with significant morbidity. This narrative review on error traps in airway management aims to highlight the common pitfalls and proposes solutions to optimize best practices for pediatric difficult airway management. We have categorized common errors of pediatric difficult airway management into three main error traps: preparation, performance, and proficiency, and present potential strategies to improve patient safety and successful tracheal intubation in infants and children with difficult airways.